Genesis of the Idea of Using Folk Arts and Crafts Elements in Teaching and Upbringing in Classical Ukrainian and Western European Pedagogical Thought - Boichenko, Maryna; Nykyforov, Andrii; Hulei, Olha (Journal of History Culture and Art Research, 2020)
The article aims to identify the origins and analyze the development of the idea of applying folk arts and crafts elements in teaching and upbringing in the works of Ukrainian and Western European classical educators. The conceptual analysis of the classical national and foreign pedagogical thought, taking into account the specificity of the studied artistic-educational phenomenon, allowed determining the foundations of scientific-theoretical understanding of decorative and applied arts as a subject of pedagogical research. In the course of the study, a positive attitude of the outstanding figures of education and culture towards the introduction of folk pedagogy elements, in particular traditional arts and crafts, was revealed, namely the views of prominent figures of Ukrainian national pedagogy, writers, philosophers (Hryhorii Skovoroda, Oleksandr Dukhnovych, Lesia Ukrainka, Ivan Franko, Anton Makarenko, Vasyl Sukhomlynskyi, Taras Shevchenko); Ukrainian and Russian teacher of Ukrainian origin Konstiantyn Ushynskyi, who first introduced the concept of “folk pedagogy” to scientific discourse; Russian Soviet scholar-teacher, researcher of Chuvash folk pedagogy, founder of the term “ethno-pedagogy” Hryhorii Volkov; Western European theorists-philosophers, scientists-pedagogues (I. Bazedov, B. Blache, H. Campe, H. Saltzman, D. Diderot, J. Comenius, J. Locke, R. Owen, J. Pestalozzi, J.-J. Rousseau, I. Heusinger). At the same time, the article analyzes the works of foreign art theorists, propagandists of the world movement for the unity of arts and crafts (G. Semper, V. Morris, A. Riegl, J. Ruskin), whose scientific-theoretical works have contributed to the improvement of the status of decorative and applied arts in the history of art education development in Ukraine in the 19th – early 20th centuries. The findings of the study traced general features of the genesis of pedagogical ideas of foreign and domestic scientists on the development of art education in the field of arts and crafts as a basis for introduction of decorative and applied arts in the institutions of art and general education in Ukraine.